Raqs al raya al masriya (O dançar da vida egípcia): uma espiritualidade do corpo - Martins, Silvia Xavier da Costa (2023)
This dissertation thesis aims to understand how spirituality is experienced within the ancestral context of the Egyptian dances’ own corporeity. The research employed oral history methodology of life – based on one of the types of methodologies oral history. Using free interviews and field journals, it sought to record accounts and interviews on dancing in the life of Egyptians. It took place in July 2022, in Egypt, more precisely in the cities of Cairo, Luxor and Aswan. The subjects of the research were native Egyptians dancers or non-dancers from diverse places and profiles, thus presenting a short term qualitative ethnographic study. A broad concept of non-religious spirituality is premise for this study and within it, the human being is perceived as a transcendental being as well as making a connection with the dancing experimentation - which some authors define it as “spirituality of the body”. When considering the Egyptian dances as “spiritualities of the body”, they become part of the research about spirituality and health in the field of Religious Studies, within which spirituality is conceived in the connection with corporeity. The analysis of the collected data shows points of intersection, suggested by the methodology, and which were name in this study as nuclei of significance. They are: the spirituality of the body within ancestral context; the dancing of the soul; “being in the world” from actual experiencing dance; culture identification; the impart of knowledge through dance and corporeity; the presence of spirituality on stage; strengthening rites and rituals through Egyptian dance; and Egyptian dances characterized as spirituality of the body. These results show the relevance of this academic study, presenting the Egyptian dances as spirituality of the body, surfacing deeper thoughts, building and creating movement, dialogue and awareness, creating a better understanding for one’s life’s journey.